Circulating PMN-MDSC level positively correlates with a poor prognosis in patients with metastatic hormone-sensitive prostate cancer - Kohada, Yuki; Kuromoto, Akito; Takeda, Kazuya; Iwamura, Hiromichi; Atobe, Yuri; Ito, Jun; Kaifu, Tomonori; Kaiho, Yasuhiro; Nakashima, Ichiro; Hinata, Nobuyuki; Nakamura, Akira; Sato, Makoto (Frontiers in Urology, 2022)
Introduction: This study aims to investigated for the first time the role of myeloid-derived suppressor cells (MDSCs) in metastatic-hormone sensitive prostate cancer (mHSPC), which has not been investigated previously. Materials and Methods: This was a prospective observational cohort study. MDSC subsets in peripheral blood samples were classified and evaluated by flow cytometry as early-stage MDSCs (e-MDSCs), polymorphonuclear MDSCs (PMN-MDSCs), and monocytic MDSCs (M-MDSCs). The prostate-specific antigen progression free survival (PSA–PFS) and overall survival (OS) were evaluated to assess the prognostic value of each of the MDSC subsets. The immune cell dynamics and gene expression alteration were analyzed by single-cell RNA-sequencing (scRNA-seq) in a representative case. Results: Thirty-one mHSPC patients and 11 healthy controls (HCs) were included in this study. There were significantly more PMN/M-MDSCs in mHSPC patients than in HCs (p <0.05) before treatment, but the numbers became similar to those in HCs after treatment. Although there were no marked differences in the high and low ratios of e-MDSCs and M-MDSCs, patients with a high ratio of PMN-MDSCs (≥0.30%) had a poorer PSA–PFS and OS than those with a low ratio (<0.30%) (p <0.05). scRNA-seq showed that the expression of genes implicated in tumor progression was upregulated in a representative mHSPC case. Conclusions: A high frequency of PMN-MDSCs correlated with poor prognosis in mHSPC patients. PMN-MDSCs and their highly expressed genes are potential novel therapeutic targets for mHSPC.